PENGARUH GOOGLE CLASSROOM DISERTAI VIDEO TERHADAP HASIL BELAJAR MATERI SPLDV DI SMP - Dea Muziani; Bistari Bistari; Rustam Rustam (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis exploration is a trial study that expects to see the impact of utilizing google classroom alongside video exercises on understudy learning results on SPLDV material in class VIII SMP Negeri 13 Pontianak. The populace in this investigation were all understudies of class VIII SMP Negeri 13 Pontianak. The example of this exploration is the understudies of class VIII H and class VIII K. Class VIII H as the control class utilizing google classrooom joined by power focuses. In the mean time, class VIII K is a test class utilizing google study hall joined by learning recordings. Information assortment instruments utilized were perception sheets and tests. The perception sheet utilized is the learning execution perception sheet. The test utilized is a trial of learning results. The pretest and posttest information were examined utilizing the t-test in the wake of satisfying the homogeneity and ordinariness test. The aftereffects of information examination show that t count> t table is 1.95> 1.73. Accordingly it very well may be inferred that there is a positive and critical impact of utilizing google study hall alongside learning recordings on understudy learning results.Keywords: Google Classroom, Learning Videos, Learning Outcomes